Variation in the number of sperm trapped on the perivitelline layer of the egg in three species of estrildid finch. (16th August 2017) - Hurley, Laura L.; Fanson, Kerry V.; Griffith, Simon C.
Abstract: Birds are physiologically polyspermic, with normal embryonic development following penetration of the inner perivitelline layer (PVL) of the ovum by multiple sperm. The PVL traps dozens to thousands of the sperm present at the time of fertilization, providing information about the number of sperm that traversed the females' reproductive tract and reached the ovum. Broadly, across avian species, the number of sperm detected on the PVL is positively related to ovum size and female body mass. However, relatively few studies have characterized the amount of variation that occurs within and between closely related species that are similar in size. We characterized variation in the average number of sperm trapped by the PVL, across species and between and within breeding pairs, in 3 similar-sized species of estrildid finch. The average number of PVL sperm changed significantly across the laying order in 2 of the species, and there was significant variation between breeding pairs in all 3 species. The variation in PVL sperm number was not always consistent within a pair across multiple breeding attempts (2 species examined). Our data highlight the need to better understand the patterns and processes of selection that optimize and alter the number of sperm reaching the ovum within and across species.